Effect of Polycystic Ovary Syndrome and Hormones Disorder on Enzymes Gammaglutamyl Transferase, Oxaloacetic Transaminase, and Proteins - Saleem, Maysoon M. Najeeb M (Al-Nahrain Journal of Science, 2017)
Polycystic ovary syndrome (PCOS) is complex metabolic disorder of endocrine gland in women of reproductive age. The present work illustrate the effect of (PCOS) and hormone disturbance on serum enzymes activities, iron status parameters and hormone profile in patient women suffering from, PCOS, acute kidney disease (AKD) with PCOS, acute kidney disease and iron deficiency anemia (IDA). A total of 160 women, include 135 patients and 25 of control apparently healthy group, patients were subdivided into four groups,(G1) consisted of 50 patients of PCOS, (G2) of 30 patients of PCOS with AKD, (G3) of 30 patient of AKD and (G4) involve 25 patients of IDA. The specimens were collected from different hospital in Baghdad city. The patients and control were investigated for enzymes, gammglutamyltrasferase (GGT), glutamic oxaloacetic transaminase (GOT) or aspartate transaminase (AST) & glutamicpyruvic transaminase (GPT) or alanine transaminase (ALT) lactate dehydrogenase (LDH), total serum proteins (TSP), albumin, globulin, total cholesterol (TC), triglyceride (TG), urea, creatinine and uric acid. Also iron status parameters (serum iron, transferrin saturation percent (TS%), transferrin concentration, and total iron binding capacity (TIBC) and ferritin concentration) were estimated. As well as hormone profile (testosterone (TT), Follicle stimulating hormone (FSH), lutinizing hormone (LH), prolactin (PL), estradiol (E), and progesterone (PRG)) were estimated Results revels highly significant increases for AST or GOT, ALT or GPT, and GGT activities P˂0.001, and a change in LDH of G1 and G2 patients were highly increased P˂0.001 as compared with normal. Remarkable rising was detected in TSP of (G1) patient while there is significant decrease in proteins level of (G2) patients in comparison with normal. Patients of (G3) show significant difference in GGT, LDH and protein. There is significant change in LDH and albumin in (G4), and no change in AST, ALT, GGT, and proteins as compared with normal. Triglyceride (TG), total cholesterol (TC), creatinine show very highly significant change for patients of (G1, G2, G3&G4). Patients women with PCOS show no remarkable change in uric acid and urea and a change in creatinine concentration. Serum iron parameters were changed significantly in patients of (G1, G2, G3, and G4) in comparison with healthy control groups. Hormones levels were significantly different in PCOS patients as compared with normal individual. In conclusion there were remarkable changes in the activities of AST, ALT, GGT, and LDH. This is the first time for the estimation of a change in LDH activity in women with (PCOS) this could be due to genetic and envirmental factor and gene mutation. Hormone levels and iron status parameter changed remarkably may be due to metabolic disturbance and abnormality in the function of hypothalamic neurotransmitter.